Penurunan Berat Badan pada Remaja Obesitas Menggunakan Hipnoterapi - Maria Tarisia Rini; Bangun Dwi Hardika; Ketut Suryani (Jurnal Keperawatan Silampari, 2020)
This study aims to determine the effect of hypnotherapy on weight loss in obese adolescents. The research design used is a quasi-experiment. The results showed that 15 respondents (68.2%) experienced weight loss, and seven respondents (31.8%) did not experience weight loss from the statistical test results obtained p-value 0.001 with a correlation coefficient value of 0.682. Also, the p-value of the chi-square test results is 0.004. In conclusion, there is a significant relationship between hypnotherapy and weight loss. Keywords: Weight Loss, Hypnotherapy, Youth